TEKNOLOGI DIGITAL SEBAGAI ALAT BANTU TERAPI ANAK ADHD: ANALISIS KUALITATIF DARI PERSPEKTIF TERAPIS - Fifin Dwi Pratiwi; Idyana Adha; Agatha Angela Praha Geraldine (Counseling Milenial (CM), 2026)
Children with special needs, especially those with Attention Deficit Hyperactivity Disorder (ADHD), require adaptive therapy services that are tailored to their developmental characteristics. The development of digital technology in the current era has opened up opportunities for the use of digital media as a tool in the therapy process for children with ADHD. This study aims to analyze the effect of digital technology use in therapy services for children with ADHD, identify the challenges faced by therapists, and formulate recommendations for the appropriate and safe use of digital technology. The study uses a descriptive qualitative approach with a case study method. The research subjects consisted of four therapists who provided therapy services to children with ADHD at a special needs child development therapy institution in Metro City, Lampung Province. Data collection techniques were carried out through in-depth interviews and direct observation, then analyzed thematically. The results showed that the use of digital media can have a positive impact in the form of increased focus, motivation, and involvement of children in therapy, as well as helping to develop self-control skills. However, the use of digital media also poses challenges and negative impacts such as the risk of excessive distraction, gadget addiction, sleep pattern disorders, and limited digital competence of therapists. Therefore, the use of digital technology in ADHD therapy needs to be planned, directed, tailored to the child's needs, and supported by direct assistance from therapists and active involvement of parents.